2018
DOI: 10.1016/j.joule.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Doped Graphene for Electrocatalytic N2 Reduction

Abstract: Boron-doped graphene with different boron structures was rationally synthesized to enhance the adsorption of N 2 , thus enabling an efficient metal-free electrocatalyst for electrochemical N 2 reduction in aqueous solution at ambient conditions. At a doping level of 6.2%, boron-doped graphene achieved a NH 3 production rate of 9.8 mg$hr À1 $cm À2 and an excellent faradic efficiency (10.8% at À0.5 V versus reversible hydrogen electrode).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
612
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 864 publications
(628 citation statements)
references
References 39 publications
13
612
0
3
Order By: Relevance
“…[8,[14][15][16][17][18][19][20][21][22][23] Specifically,b enefiting from the unoccupied and occupied dorbitals of transition metals,t he electron density from N 2 is synergically accepted with appropriate energy and symmetry,a nd then, the transition metal donates electrons to the p*o rbital of NN, strengthening N 2 adsorption and weakening the NNbond. [29] Similar nitrogen reduction activity was also observed on metal-free boron carbide nanosheets. [24] Compared to transition metals,t he weak hydrogen adsorption of nonmetallic elements and their abundant valence electrons should provide am ore ideal nitrogen activation center.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…[8,[14][15][16][17][18][19][20][21][22][23] Specifically,b enefiting from the unoccupied and occupied dorbitals of transition metals,t he electron density from N 2 is synergically accepted with appropriate energy and symmetry,a nd then, the transition metal donates electrons to the p*o rbital of NN, strengthening N 2 adsorption and weakening the NNbond. [29] Similar nitrogen reduction activity was also observed on metal-free boron carbide nanosheets. [24] Compared to transition metals,t he weak hydrogen adsorption of nonmetallic elements and their abundant valence electrons should provide am ore ideal nitrogen activation center.…”
supporting
confidence: 58%
“…[25,26] Some recent studies have shown that the use of nonmetallic components as active centers may be an effective way to obtain high selectivity. [29] Similar nitrogen reduction activity was also observed on metal-free boron carbide nanosheets. [29] Similar nitrogen reduction activity was also observed on metal-free boron carbide nanosheets.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…[1][2][3][4] From an energy-saving perspective,g reen N 2 to NH 3 fixation methods are strongly desired because the main industrial process for producing NH 3 -the Haber-Bosch process-requires extremely harsh reaction conditions (400-600 8 8C, 20-40 MPa) and causes pollution and greenhouse gas emissions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts.…”
mentioning
confidence: 99%